Can private food standards promote gender equality in the small farm sector? - Eva-Marie Meemken; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
Agricultural commercialization can help to lift subsistence farmers out of poverty, but can also have adverse effects on gender equality. We explore whether private food standards - with their particular elements to regulate production and trade - could serve as a vehicle to promote gender equality in the small farm sector. We use gender-disaggregated data from coffee producers in Uganda and focus on two sustainability standards that explicitly address gender issues, namely Fairtrade and UTZ. Entropy balancing techniques, combined with estimates of farmers' willingness to accept standards, are used to control for possible selection bias when comparing certified and non-certified households. We find that standards and their certification programs increase wealth in male-headed and female-headed households. In male-headed households, standards also change the intra-household distribution of asset ownership: while in non-certified households, assets are predominantly owned by the male household head alone, in certified households most assets are jointly owned by the male head and his female spouse. Standards also improve access to agricultural extension for both male and female farmers. Effects on women's access to financial services are statistically insignificant. Private standards cannot completely eliminate gender disparities, but the findings suggest that they can contribute towards this goal.
Keywords: 330; cash crops; certification; gender; sustainability standards; women's empowerment